2021
DOI: 10.1111/os.12937
|View full text |Cite|
|
Sign up to set email alerts
|

Age‐ and Gender‐Specific Epidemiologic Characteristics of Major Intra‐Articular Fractures: Five‐Year Data from a Level 1 Trauma Center

Abstract: Objective To investigate the epidemiological characteristics of major intra‐articular fractures. Methods This retrospective study enrolled patients with major intra‐articular fractures who were treated in the Third Hospital of Hebei Medical University from January 2015 to December 2019. A total of 11,084 patients (7,338 [66.20%] males and 3,746 [33.80%] females) meeting the inclusion and exclusion criteria were included. The distribution characteristics of intra‐articular fractures involving shoulder, elbow, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This device gives a lower load than a traditional traction table. Zhao et al [14] studied the epidemiological characteristics of large intra-articular fractures. The study revealed age and gender epidemiological characteristics of large intra-articular fractures, which became the basis for clinical assessment and practice.…”
mentioning
confidence: 99%
“…This device gives a lower load than a traditional traction table. Zhao et al [14] studied the epidemiological characteristics of large intra-articular fractures. The study revealed age and gender epidemiological characteristics of large intra-articular fractures, which became the basis for clinical assessment and practice.…”
mentioning
confidence: 99%
“…In [1], Wei‐guang Zhao's first affiliation was omitted in error. To correct this, the order of the affiliations have to be adjusted and all authors' affiliations have to be accordingly renumbered.…”
mentioning
confidence: 99%